Immune subversion by Mycobacterium tuberculosis through CCR5 mediated signaling: involvement of IL-10. - Shibali Das; Sayantan Banerjee; Saikat Majumder; Bidisha Paul Chowdhury; Avranil Goswami; Kuntal Halder; Urmita Chakraborty; Nishith K Pal; Subrata Majumdar (PLoS ONE)
Tuberculosis is characterized by severe immunosuppression of the host macrophages, resulting in the loss of the host protective immune responses. During Mycobacterium tuberculosis infection, the pathogen modulates C-C Chemokine Receptor 5 (CCR5) to enhance IL-10 production, indicating the possible involvement of CCR5 in regulation of the host immune response. Here, we found that Mycobacterium infection significantly increased CCR5 expression in macrophages there by facilitating the activation of its downstream signaling. These events culminated in up-regulation of the immunosuppressive cytokine IL-10 production, which was further associated with the down-regulation of macrophage MHC-II expression along with the up-regulation of CCR5 expression via engagement of STAT-3 in a positive feedback loop. Treatment of macrophages with CCR5 specific siRNA abrogated the IL-10 production and restored MHCII expression. While, in vivo CCR5 silencing was also effective for the restoration of host immune responses against tuberculosis. This study demonstrated that CCR5 played a very critical role for the immune subversion mechanism employed by the pathogen.